Incidence of occupational latent tuberculosis infection in South African healthcare workers - Adams, Shahieda (Eur Respir J, 2015)
The test-specific incidence of latent tuberculosis infection (LTBI) in healthcare workers from sub-Saharan Africa is unknown. 505 healthcare workers from South Africa were screened at baseline, and after 12 months, with a questionnaire, the tuberculin skin test (TST), and two T-cell assays (T-SPOT.TB and QuantiFERON-TB Gold-In-Tube). Test-specific conversion rates were calculated. The prevalence of presumed LTBI at baseline was 84, 69 and 62% using the TST, QuantiFERON-TB Gold-In-Tube and T-SPOT.TB, respectively. The annual test-specific conversion rate, depending on the cut-off point used, was as follows: TST 38%; QuantiFERON-TB Gold-In-Tube 13–22%; and T-SPOT.TB 18–22%. Annual reversion rates were 4, 7 and 16%, respectively. The annual TST conversion rate was significantly higher than that derived from published local community-based data (IRR 3.53, 95% CI 1.81–6.88). Factors associated with conversion (any test) included healthcare sector of employment, counselling of tuberculosis patients, and a baseline positive TST (for T-SPOT.TB). The annual rate of tuberculosis infection in South African healthcare workers was very high, irrespective of the testing method used, and may be explained by occupational exposure, as the rate was considerably higher than non-healthcare workers from the same community. Collectively, these data support the need for implementation of tuberculosis-specific infection control measures in Africa.